2016
DOI: 10.1063/1.4948329
|View full text |Cite
|
Sign up to set email alerts
|

Effect of van der Waals interactions on the stability of SiC polytypes

Abstract: Density functional theory calculations with a correction of the long-range dispersion force, namely the van der Waals (vdW) force, are performed for SiC polytypes. The lattice parameters are in good agreement with those obtained from experiments.Furthermore, the stability of the polytypes in the experiments, which show 3C-SiC as the most stable, are reproduced by the present calculations. The effect of the vdW force on the electronic structure and the stability of polytypes are discussed. We observe that the v… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
16
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 40 publications
7
16
1
Order By: Relevance
“…Hence, 3C-SiC turns out to be the most stable polytype. This is well in agreement both with experimental evidences inferring 3C-SiC as the most stable SiC structure in the nuclear stage [37] and with a recent theoretical work [29]. Nevertheless, the predicted energetic hierarchy at T=0K is still not sufficient to understand the competition in stability of SiC polytypes at higher temperature, as probed experimentally [16][17][18][19][20]27].…”
supporting
confidence: 88%
See 1 more Smart Citation
“…Hence, 3C-SiC turns out to be the most stable polytype. This is well in agreement both with experimental evidences inferring 3C-SiC as the most stable SiC structure in the nuclear stage [37] and with a recent theoretical work [29]. Nevertheless, the predicted energetic hierarchy at T=0K is still not sufficient to understand the competition in stability of SiC polytypes at higher temperature, as probed experimentally [16][17][18][19][20]27].…”
supporting
confidence: 88%
“…Recently it was shown that density functional theory (DFT) calculations [28] including the van der Waals (vdW) correction do predict the 3C phase to have the lowest free energy at T=0K [29]. This intriguing result points out the importance of considering long-range interactions when comparing different SiC polytypes.…”
mentioning
confidence: 99%
“…The literature on the thermodynamic stability and polytypes of SiC is rich. Many theoretical works were carried out to explain the band structure and total energies of the various polytypes of silicon carbide [22][23][24], showing that, at a high temperature, the 6H-and 4H-SiC polytypes become thermodynamically more stable than 3C-SiC [15]. In particular, the formation energies of SFs in 3C-SiC decrease with the temperature (particularly for ESFs).…”
Section: Resultsmentioning
confidence: 99%
“…The polytypism arising from different stacking of the Si and C atomic layers is known to be a key factor in understanding the physical properties of SiC 4 . The cubic 3C‐SiC, with the so‐called β‐SiC crystal structure, is recognized as the most stable polytype, as confirmed by recent free energy calculations 5,6 . Moreover, the knowledge of extended defect formation such as stacking faults (SFs) and twins in the various polytypes is an important issue for use in electronic devices, since these defects can significantly modify the band structure and deteriorate their electronic properties 7,8 .…”
Section: Introductionmentioning
confidence: 99%
“…4 The cubic 3C-SiC, with the so-called β-SiC crystal structure, is recognized as the most stable polytype, as confirmed by recent free energy calculations. 5,6 Moreover, the knowledge of extended defect formation such as stacking faults (SFs) and twins in the various polytypes is an important issue for use in electronic devices, since these defects can significantly modify the band structure and deteriorate their electronic properties. 7,8 Moreover, 4H/6H SiC-based devices were found to degrade under operation due to partial Shockley SF formation and expansion.…”
Section: Introductionmentioning
confidence: 99%